Understanding high-quality development of marine economy in China: A literature review - Aiwu Zhao; Hongjun Guan; Zhenzhen Sun (Marine Economics and Management (MAEM), 2019)
Purpose - High-quality development of marine economy is a new concept put forward in response to the current national strategy in China. The purpose of this paper is to thoroughly understand the connotation and significance of high-quality development of marine economy through literature review, and further analyze the prospects for further research. Design/methodology/approach - The authors first use the information visualization technology of CiteSpace to present a systematic review of the published literature from 2010 to 2019. Then, the authors analyze the researches on high-quality development of marine economy in terms of connotation, evaluation dimension, development path and guarantee mechanism. Findings - Analysis results show that there is still insufficient understanding of the differences and links between the high-quality development of marine economy and the construction of marine power, intelligent ocean and transparent ocean. Originality/value - Based on a thorough understanding of the subject, this paper puts forward the direction of further research on evaluation index system, path design scheme and policy system construction for highquality development of marine economy.
Keywords: 330; Knowledge mapping; CiteSpace; Marine economy; High-quality development